Theory of Bridge Aerodynamics - Strømmen, Einar (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This text book is intended for studies in structural dynamics or wind engineering, with special focus on the stochastic theory of wind induced dynamic response calculations for slender bridges or other line- like civil engineering type of structures. It contains the background assumptions and hypothesis as well as the development of the computational theory that is necessary for the prediction of wind induced fluctuating displacements and cross sectional forces. The book contains detailed and complete examples of relevant cases that are useful for the understanding and the practical application of the theory. The text is at an advanced level in the sense that it requires some knowledge of basic structural dynamics, particularly of solution procedures in a modal format.